Contribution of hydrogeochemical and statistical tools to the acquisition of water quality in the Bouchegouf Plain (northeast Algeria) - Habiba Majour; Nassima Sedrati; Samir Hani; Badra Attoui; Samia Bounab; Azzedine Hani (Water Supply, 2023)
The Bouchegouf Plain is an industrial and mainly agricultural region. The results of analyses revealed high concentrations of physicochemical and bacteriological parameters in surface and underground waters. The objective of this research is to study the impact of the various discharges on water and the environment. Physicochemical and bacteriological analysis methods are used to characterize the surface and groundwaters. The synthesis of geological, hydrogeological and physicochemical data made it possible to develop models of underground flows and to delimit the perimeters of protection of the wells. The results showed a significant threat to the environment (Mellah and Seybouse streams) and to the waters of the alluvial aquifer. Indeed, the high concentrations of physicochemical and bacteriological parameters, in particular at the point of discharge of the yeast plant, can have harmful effects on fauna, flora and human health (waterborne diseases). Simulations of groundwater flows and pollutant transfer showed that groundwater is strongly affected by the drainage of the Seybouse wadi. Road traffic can also be the source of accidental pollution. HIGHLIGHTS Groundwater quality is based on the physical and chemical parameters that are influenced by geological formations.; The methodology used for the processing of the analysis results is based on multivariate statistical methods.; The integration of statistical approaches and geochemical methods was applied to investigate the regional factors and processes governing the chemical composition of water in the study area.;